2019
DOI: 10.7567/1347-4065/ab003b
|View full text |Cite
|
Sign up to set email alerts
|

Impact of size distributions of Ge islands as etching masks for anisotropic etching on formation of anti-reflection structures

Abstract: The impact of the size distributions of Ge islands on the structural and optical characteristics of anti-reflection structures was investigated. The variation of island size distribution was achieved through the variation of growth temperature in gas-source molecular beam epitaxy at 700 °C-800 °C. Ge islands were utilized as etching masks to form the anti-reflection structures. By using lower growth temperature of 700 °C and subsequent etching, larger texture without many hollows was formed in contrast to that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
5
0
1
Order By: Relevance
“…[15] Ohta et al reported that Si nanopyramids with a size of 400-600 nm can be formed uniformly by using self-assembled Ge islands as etching masks. [16] Similarly, Zhong et al reported that Ag NPs predeposited on Si wafers by a solution process can be used as etching masks for the following alkaline etching process. [17,18] From the industrial DOI: 10.1002/solr.202200707…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[15] Ohta et al reported that Si nanopyramids with a size of 400-600 nm can be formed uniformly by using self-assembled Ge islands as etching masks. [16] Similarly, Zhong et al reported that Ag NPs predeposited on Si wafers by a solution process can be used as etching masks for the following alkaline etching process. [17,18] From the industrial DOI: 10.1002/solr.202200707…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] Ohta et al reported that Si nanopyramids with a size of 400–600 nm can be formed uniformly by using self‐assembled Ge islands as etching masks. [ 16 ] Similarly, Zhong et al reported that Ag NPs predeposited on Si wafers by a solution process can be used as etching masks for the following alkaline etching process. [ 17,18 ] From the industrial perspective, however, the etching process should be as simple as possible because the multistep approaches are generally complex and may require additional process equipment.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of optoelectronic devices, such as solar cells and photodetectors, depends on their surface properties related to light reflection and transmission 1 , 2 . To reduce reflection, surface texturing and coating with antireflection dielectric films are usually used 3 , 4 . Recently, intensive research has been carried out on coatings of metal and/or dielectric particles as an alternative to continuous antireflection films 5 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, these structures can be applied for modification of surfaces and the formation of coatings [9,10]. They can be used for creation of textured surfaces, anti-reflection coatings [11] and implementation of photonic crystals and microresonators [12], as well as in quantum information technologies [13].…”
Section: Introductionmentioning
confidence: 99%